Pepper fruit (Dennettia tripetala [annonaceae]) seed inhibits uterine contractions via blockade of intracellular calcium release and extracellular calcium influx in ex vivo studies - Uchendu, Adaeze; Bafor, Enitome (Journal of Current Biomedical Research, 2023)
Dennettia tripetala (DT) is a tree found in rain forest belt of Nigeria, Cameroon and Ivory Coast. The seed is commonly used in preparing food for mothers after delivery because it is believed to play a role in postpartum uterine contraction. There is however no scientific evidence validating this claim. Hence, the study aimed to investigate the effects of DT seed on non-pregnant and pregnant uterus using mouse model. The dried seeds of DT were macerated in methanol and the effects of DT extract were investigated on uterus tissues isolated from non-pregnant and pregnant mice. DT extract was examined on spontaneous uterine contraction, contractions induced by oxytocin, and high potassium chloride (KCl)-induced depolarization. Its effect was also evaluated on calcium ion (Ca2+) release from internal stores. The DT extract suppressed spontaneous uterine contractility in both pregnant and non-pregnant uterus in a concentration-dependent manner. It significantly inhibited uterine contractions elicited by high KCl and oxytocin-induced contractions in both pregnant and non-pregnant uterus. The extract also inhibited uterine contractility induced by oxytocin in the Ca2+-free medium in pregnant and non-pregnant uterus. The study has provided scientific evidence that DT seed extract has uterine relaxing effect in both pregnant and non-pregnant mouse uterus possibly by blocking intracellular Ca2+ released and influx of extracellular Ca2+. The result has shown that DT has no benefit in reducing the risk of post-partum hemorrhage, however, it may have potential benefits in management of dysmenorrhea and preterm labour in non-gravid and gravid uteri respectively.